Allan King's A Married Couple - Druick, Zoë (Book collections on Project MUSE., 2010)
In Allan King's A Married Couple, Zoë Druick examines the film in the context of late 1960s cinematic and cultural movements. Through a scene-by-scene synopsis and an analysis of contemporary responses to the piece, she traces A Married Couple's influence on documentary and Canadian filmmaking. This work is an accessible and engaging introduction to a controversial film and its fascinating director."--Pub. desc.